The Biological Function of the Prion Protein: A Cell Surface Scaffold of Signaling Modules - Linden, Rafael (Frontiers in Molecular Neuroscience, 2017)
The prion glycoprotein (PrPC) is mostly located at the cell surface, tethered to the plasma membrane through a glycosyl-phosphatydil inositol anchor. Misfolding of PrPC is associated with the transmissible spongiform encephalopathies, whereas its normal conformer serves as a receptor for oligomers of the β-amyloid peptide, which play a major role in the pathogenesis of Alzheimer’s Disease. PrPC is highly expressed in both the nervous and immune systems, as well as in other organs, but its functions are controversial. Extensive experimental work disclosed multiple physiological roles of PrPC at the molecular, cellular and systemic levels, affecting the homeostasis of copper, neuroprotection, stem cell renewal, and memory mechanisms, among others. Often each such process has been heralded as the bona fide function of PrPC, despite restricted attention paid to a selected phenotypic trait, associated with either modulation of gene expression or to the engagement of PrPC with a single ligand. In contrast, the glycosyl-phosphatydil inositol-anchored prion protein was shown to bind several extracellular and transmembrane ligands, which are required to endow that protein with the ability to play various roles in transmembrane signal transduction. In addition, differing sets of those ligands are available in cell type- and context-dependent scenarios. To account for such properties, we proposed that PrPC serves as a dynamic platform for the assembly of signaling modules at the cell surface, with widespread consequences for both physiology and behavior. The current review advances the hypothesis that the biological function of the prion protein is that of a cell surface scaffold protein, based on the striking similarities of its functional properties with those of scaffold proteins involved in the organization of intracellular signal transduction pathways. Those properties are: the ability to recruit spatially restricted sets of binding molecules involved in specific signaling; mediation of the crosstalk of signaling pathways; reciprocal allosteric regulation with binding partners; compartmentalized responses; dependence of signaling properties upon posttranslational modification; and stoichiometric requirements and/or oligomerization-dependent impact on signaling. The scaffold concept may contribute to novel approaches to the development of effective treatments to hitherto incurable neurodegenerative diseases, through informed modulation of prion protein-ligand interactions.